Pemanfaatan Aplikasi Kahoot Sebagai Sarana Ujian Berbasis Online - Fince Tinus Waruwu; Bister Purba; Dito Putro Utomo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In improving the quality and quality of learning in educational institutions, technological development is needed in achieving that goal. Especially in the Lower STM 1 High School at the moment trying to take advantage of technological developments to meet the expected goals. Manual exams conducted at SMA Negeri 1 STM Hilir have many obstacles such as the possibility of fraud committed by students when answering exams and require additional time for the teaching staff to check students' test results. Kahoot is a learning media application, where by using kahoot the manual examination process can be changed to online. Therefore, community service conducted by the team is to conduct training in the use of the Kahoot application instead of a manual exam.